2019
DOI: 10.7577/hrer.3079
|View full text |Cite
|
Sign up to set email alerts
|

Children’s rights and teachers’ responsibilities: reproducing or transforming the cultural taboo on child sexual abuse?

Abstract: Enhancing young learners’ knowledge about appropriate and inappropriate sexual behaviour is crucial for the protection of children’s rights. This article discusses teachers’ understandings of their practices and approaches to the topic of child sexual abuse in Norwegian upper secondary schools, based on phone interviews with 64 social science teachers. Countering child sexual abuse is a political priority for the Norwegian government, and the Committee on the Rights of the Child acknowledges several state init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 8 publications
4
12
0
Order By: Relevance
“…The report stresses the need for systematic teaching of sexual health on all levels of the education system as a measure to prevent sexual abuse and HSB among children (Askeland et al, 2017). Such recommendations concur with the broader international debate on teachers' and schools' role in prevention of sexual abuse (Carmody, 2009;Flood et al, 2009;Goldschmidt-Gjerløw, 2019;Letourneau et al, 2017;McKibbin et al, 2016;Sprott et al, 2005).…”
Section: Scope Of the Problemsupporting
confidence: 69%
“…The report stresses the need for systematic teaching of sexual health on all levels of the education system as a measure to prevent sexual abuse and HSB among children (Askeland et al, 2017). Such recommendations concur with the broader international debate on teachers' and schools' role in prevention of sexual abuse (Carmody, 2009;Flood et al, 2009;Goldschmidt-Gjerløw, 2019;Letourneau et al, 2017;McKibbin et al, 2016;Sprott et al, 2005).…”
Section: Scope Of the Problemsupporting
confidence: 69%
“…Teaching practices pertaining to various forms of child maltreatment are most likely influenced by factors such as cultural taboos and the personal characteristics of individual teachers. 45 , 46 As such, there appears to be too much room for individual interpretation in the field of, for example, sexual abuse. 46 …”
Section: Discussionmentioning
confidence: 99%
“…There appears to prevail a cultural taboo regarding teaching about sexual violence, especially when it targets children and adolescents. In my own study (Goldschmidt-Gjerløw, 2019), I have found that child sexual abuse and rape among young peers are the least addressed topics related to sexual violence in upper secondary school. Still, there is not enough knowledge regarding why some teachers bring these matters into upper secondary classrooms, whereas others do not or do so to a little extent.…”
Section: Introductionmentioning
confidence: 93%
“…Sexuality education has gained attention in Norway and worldwide over the last decade (Hind, 2016;Røthing & Bang Svendsen, 2009;Støle-Nilsen, 2017;Stubberud et al, 2017;Goldschmidt-Gjerløw, 2019;United Nations Educational, Scientific and Cultural Organization, 2018). Research in the field of Norwegian sexuality education focuses on teachers' understandings and perceptions of practice in either secondary school from 8th to 10th grade (Røthing & Bang Svendsen, 2009;Støle-Nilsen, 2017) or from 1st to 10th grade (Hind, 2016;Stubberud et al, 2017), whereas less research has been done in upper-secondary schools (Goldschmidt-Gjerløw, 2019). In 2008, Røthing & Bang Svendsen conducted a survey among 11 school leaders, 10 school nurses and 24 teachers in secondary schools in Mid-Norway (N = 45) (Røthing & Bang Svendsen, 2008, author's translation).…”
Section: Introductionmentioning
confidence: 99%